1985
DOI: 10.1029/jb090ib12p10393
|View full text |Cite
|
Sign up to set email alerts
|

The Steens Mountain (Oregon) geomagnetic polarity transition: 1. Directional history, duration of episodes, and rock magnetism

Abstract: The thick sequence of Miocene lava flows exposed on Steens Mountain in southeastern Oregon is well known for containing a detailed record of a reversed‐to‐normal geomagnetic polarity transition. Paleomagnetic samples were obtained from the sequence for a combined study of the directional and intensity variations recorded; the paleointensity study is reported in a companion paper. This effort has resulted in the first detailed history of total geomagnetic field behavior during a reversal of polarity. A comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
161
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(171 citation statements)
references
References 55 publications
10
161
0
Order By: Relevance
“…Assuming that the secular variation rate during the mid-Miocene was similar to that during the Holocene and that there are no major time gaps in the El Paso section, we can use the cumulative angular VGP path and the average angular change of the VGP for southern Europe (5°/100 years according to Mankinen et al [1985]) for the calculation of the time interval and the accumulation rate of the lavas. This procedure was conducted for several directional intervals (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming that the secular variation rate during the mid-Miocene was similar to that during the Holocene and that there are no major time gaps in the El Paso section, we can use the cumulative angular VGP path and the average angular change of the VGP for southern Europe (5°/100 years according to Mankinen et al [1985]) for the calculation of the time interval and the accumulation rate of the lavas. This procedure was conducted for several directional intervals (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…C-TP1 to C-TP6 R 24.7 4.9 3.2 500 C-TP10 to C-TP24 R 123.4 10.3 1.3 2500 C-TP29 to C-TP42 R 140.4 11.7 1.7 2800 C-TP48 to C-TP61 I 86.4 7.9 2.3 1730 C-TP82 to C-TP89 N 41.2 5.9 4.5 820 a Accumulation rates of lavas and covered time intervals of five directional periods are during the EL Paso sequence. The accumulation rates were calculated using the Holocene angular change rate of the VGP track for southern Europe [Mankinen et al, 1985]. Additionally, the cumulative VGP path and the average path lenght between individual flows are given.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such paleomagnetic records from lava sequences are usually very reliable owing to the stable nature of the remanence of volcanic rocks, and absolute paleointensities can often be recovered also. Good examples are the studies of the transitional field as illustrated in the studies of the Steens Mountain lavas in Oregon (Mankinen et al, 1985). Even if the lava accumulation rate is low and random, the dataset may still give a good opportunity to study the statistical features of the geomagnetic field as shown in the studies of the Icelandic lavas (e.g., Kristjansson, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Paleomagnetic secular variation (PSV) analysis has been employed to constrain the eruption frequency down to the millennium or century timescale, and to identify the eruption pulses in some LIPs (Makinen et al 1985;Riisager et al 2003;Knight et al 2004;Chenet et al 2008;Pavlov et al 2011;Courtillot and Fluteau 2014). The geomagnetic field exhibits secular variation, both in direction and intensity, in timescales of decades to a century.…”
Section: Introductionmentioning
confidence: 99%